Brain-derived neurotrophic factor is associated with coronary macrophage infiltrates in patients with acute coronary syndrome. (25th November 2020) - Montone, R.A; Camilli, M; Russo, M; Del Buono, M; Gurguglione, F; Meucci, M.C; Rinaldi, R; Iannaccone, G; Canonico, F; Liuzzo, G; Niccoli, G; Crea, F
Abstract: Background: Brain-derived neurotrophic factor (BDNF) is a neurotrophine that plays a key role in the regulation of both central and peripheral nervous system. Moreover, BDNF is secreted in multiple tissues and exerts systemic, autocrine, and paracrine effects in the cardiovascular system. Of importance, BDNF expression was enhanced in macrophages and smooth muscle cells in atherosclerotic coronary arteries and may be involved in thrombus formation. Thus, BDNF has been suggested as an important link between inflammation and thrombosis, potentially involved in the pathogenesis of acute coronary syndrome (ACS). Purpose: In our study we aimed at assessing serum levels of BDNF in patients with ACS, evaluating differences according to clinical presentation [ST-segment elevation myocardial infarction (STEMI) vs. Non-ST-segment elevation ACS (NSTE-ACS)]. Moreover, we assessed the presence of optical coherence (OCT)-defined macrophage infiltrates (MØI) in the culprit vessel of ACS patients and evaluated their relationship with BDNF levels. Methods: ACS patients were prospectively selected. Blood samples were collected at admission and serum levels of BDNF were subsequently assessed. Presence of OCT-defined MØI along the culprit vessel was assessed. Results: 166 ACS patients were enrolled [mean age 65.3±11.9 years, 125 (75.3%) male, 109 STEMI, 57 NSTE-ACS]. Serum levels of BDNF were higher among STEMI patients compared with NSTE-ACS [median (IQR) 2.48 pg/mL (1.54–3.34) vs. 2.12 pg/mL (1.34–2.47), p=0.007], while C-reactive protein levels did not differ between the two groups. OCT assessment was performed in 53 patients and MØI were detected in 27 patients. Of importance, patients with MØI in the culprit vessel had higher levels of BDNF compared with patients without MØI [median (IQR) 2.23 pg/mL (1.38–2.53) vs. 1.41 pg/mL (0.93–2.07), p=0.023], while C-reactive protein levels did not differ between the two groups. Of note, at multivariate regression analysis BDNF levels were independent predictor of MØI [OR: 2.20; 95% CI (1.02–4.74), p=0.043]. Conclusions: Serum levels of BDNF may reliable identify the presence of local macrophage inflammatory infiltrates in patients with ACS. Moreover, BDNF levels are higher in patients with STEMI compared with NSTE-ACS. Taken together, these data suggest that BDNF may represent an interesting link between local inflammatory activation and enhanced thrombosis in ACS. Funding Acknowledgement: Type of funding source: None